Ser bilaquiano: um patrimônio cultural da memória coletiva na educação em Santa Maria – um estudo documental do Instituto Estadual de Educação Olavo Bilac - Machado, Patrícia Fabiane Nanthal (2022)
The present Master’s dissertation in Cultural Heritage, in the concentration area History and Cultural Heritage, in the research line of Archival Documentary Heritage, is directly related with intangible cultural heritage, as it investigates the relations of belonging and identity, defined in this study as “being bilaquian”, among former teacher and former students of the State Institute of Education Olavo Bilac. Bilac, as the Institute is known, over its 120 years of existence, has established itself as one of the most significant educational agents in the city. Its influence has been of fundamental importance to the history of Santa Maria, since it helped in the mobilization of groups and social strata, highlighted the performance of subjects in a context of social diversity, as well as promoting cultural meetings, with its potential to re-signify values and representations. The study approaches the theme about “being bilaquian” as a cultural heritage and how its social and political relations constitute a collective memory in the education scenario in Santa Maria. This study, in methodological terms, has the characteristic of being a research of qualitative approach, as it is related to the analysis of the archive of written documents, besides counting on photos and objects belonging to the Historical Collections of the State Institute of Education Olavo Bilac, kindly provided as a source for this research. In addition, a virtual questionnaire was conducted with the former Bilaquians who, by answering the request, could identify themselves, in different contexts, as subjects who conceive what it is to “be bilaquian”. In the meantime, we selected the answers that converged with the objective of this work and that, in a certain way, reflected the different experiences that, as a whole, would indicate a sample of what would answer “being a Bilaquian”, in its multiple facets. At the same time, we tried, through the suggested methodology, to give an identity character that would be relevant both to the dissertation and to the academy.